MENGUNGKAP MAKNA TRADISI RUWAT RUMAH DAN RUWAT BUMI DI KAMPUNG KASEPUHAN JAGARAKSA: Revealing The Meaning of the Ruwat Rumah and Ruwat Bumi Traditions In Kasepuhan Jagaraksa Village - Mohamad Imam Kamaludin; AMILIA LESTARI (Hasanuddin Journal of Sociology (HJS), 2025)
This tradition represents a form of local wisdom that reflects a harmonious relationship between humans, nature, and spirituality. This study aims to uncover the meaning behind the Ruwat Rumah and Ruwat Bumi traditions, which are still preserved by the community of Kasepuhan Village, Jagaraksa Village, Muncang District, Lebak Regency, Banten Province. Through a qualitative approach, the study collected data from in-depth interviews with traditional leaders and local residents, as well as direct observations of the ritual practices. The findings reveal that Ruwat Rumah and Ruwat Bumi not only serve as religious rituals but also function as mediums to maintain ecological balance and uphold social values in daily life.